(3GdTYQGA GdUYGdjc (B:s (3aj GdYUQ GdYHGSj GdChd (B/s - (3YWhGf, MSjfs ((3HjQhJ (B:s (3OGQ GdWdjYI ddWHGYI h GdfTQ ,s, 2000)
(3jKHJ gPG GdcJGH Gf GdTYQGA GdUYGdjc aj GdYUQ GdYHGSj GdGhd GdOjf cGf GdHGMKhf GdbOeGA efge h GdeMOKhf aj ZadI Yfge bO hbahG afge ddJYHjQ Yf Gge GdeTGcd GdGLJeGYjI h GTOgG NWQG aOaYhG HPdc Yf GdTYQ GdYQHj YUQFO GdJgeI GdJj Qej HgG ajg h aj GdYUhQ GdGOHjI GdSGHbI h GddMbI h gj GdJUGbg HGdMdaGA h GdhRQGA h MhGTjge HYjOG Yf GdLeGgjQ h eTGcdgG h GeGdgGs
Keywords: (3GdTYQs; (3GdYUQ GdYHGSjs; (3GdCOH GdYQHjs